Scientific Overview: 2013 BBC Plenary Symposium on Tobacco Addiction - De Biasi, M. (Drug Alcohol Depend, 2014)
Nicotine dependence plays a critical role in addiction to tobacco products, and thus contributes to a variety of devastating tobacco-related diseases (SGR 2014). Annual costs associated with smoking in the US are estimated to be between $289 and $333 billion. Effective interventions for nicotine dependence, especially in smokers, are a critical barrier to the eradication of tobacco-related diseases. This overview highlights research presented at the Plenary Symposium of Behavior, Biology and Chemistry: Translational Research in Addiction Conference (BBC), hosted by the UT Health Science Center San Antonio, on March 9–10, 2013. The Plenary Symposium focused on tobacco addiction, and covered topics ranging from basic science to national policy. As in previous years, the meeting brought together globally-renowned scientists, graduate student recruits, and young scientists from underrepresented populations in Texas and other states with the goal of fostering interest in drug addiction research in young generations.